If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(2x-9)=5x+16-52+3x
We move all terms to the left:
4(2x-9)-(5x+16-52+3x)=0
We add all the numbers together, and all the variables
4(2x-9)-(8x-36)=0
We multiply parentheses
8x-(8x-36)-36=0
We get rid of parentheses
8x-8x+36-36=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 20+b=4b-7 | | 6-4v=-8-6v | | (9/8x)+(7/4)=0 | | -(f-6)+-6=-3 | | (4x+3)+(x-9)=90 | | (9x/8)+(7/4)=0 | | 5x2=1 | | H-18=-2h | | x-650=437 | | 24-3a=5a | | -4x+9+6x=9 | | 4x2+76=32 | | 2(n+4)=4n-5 | | (3k+4)(9k+5)=(3k+4)(9k+5) | | 14u+-8u+1=-11 | | 13-9d=-6d-17 | | 106+4.95x=239.65 | | x/x=1,45 | | 72=b-16 | | 8+3x+4x=64 | | 5p+5+4p=6p-4 | | 5k-4=2k+7 | | 4/n=22 | | 123+-11x=76 | | 4x+5+9x=3-2(x-3) | | -10d-9=-5d+5-7d | | -5+4x+3x=-40 | | 10+3(x+2)=36 | | 14/z=70/33 | | 4(x+3)=32-x | | 6a=4a+18 | | 10+0.5x=47.5 |